INOVASI PEMBELAJARAN ILMU PENGETAHUAN ALAM (NARRATIVE LITERATUR REVIEW) - Erwinsyah, Alfian; Yusuf, Frida Maryati; Gintulangi, Selastri (Irfani, 2023)
This study aims to analyze research trends on Natural Science (IPA) learning innovations. This research method uses literature studies. Research data was obtained, from 17 articles selected through the Harzings Publish or Perish application or through the web springeropen.com and sciencedirect.com on the topic of science learning innovation with keywords that have been determined from initial studies, namely the Blended Learning learning model, Augmented Reality, Virtual Laboratory / Virtual Reality and the STEAM approach from 2018 to 2021. The results of data analysis show that the use of Augmented Reality in learning, the use of Blended Learning learning models, the use of virtual laboratories in learning, and the use of STEM-STEAM approaches in learning through 17 journal articles, all of which are solely to overcome/solve student learning problems such as interests, motivation, learning outcomes, thinking skills. Based on research, these four innovations are significant in improving students' abilities in learning science. Keywords: Literature Review, Learning Innovation, Science, Augmented Reality, Blended Learning, Virtual Laboratory, STEAM